(untitled) (Proceedings of International Educators Conference, 2024)
Political improvement of public life, democratization of management and control bodies are naturally based on political modernization. In the process of political modernization, new political institutions are created, and existing political institutions are improved and acquire a new meaning. In such conditions, on the one hand, maintaining political stability, which is an important condition for social development, becomes an objective necessity, and on the other hand, it is necessary to expand the possibilities of increasing political participation and activity of citizens. Therefore, the ongoing reforms, updates and modernization processes are one of the most important issues in the political life of Uzbekistan. In this article, the specific characteristics of political processes in Uzbekistan are analyzed on a scientific basis.